1986
DOI: 10.3109/10826088609077256
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Seven School-Based Prevention Programs: A Final Report on the Napa Project

Abstract: Described is a series of evaluation studies of seven school-based prevention programs, including four generic in-service teacher-training programs, two alternatives programs, and a drug education course. The programs were delivered to elementary or junior high students, and were evaluated individually and in several combinations or sequences, using rigorous research procedures and a comprehensive set of process and outcome measures. Only the drug education course showed any pattern of significant effects, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…Drug use prevention programs are usually evaluated with longitudinal designs, which facilitate assessment of longterm program impact (Botvin et al, 1980;Evans et al, 1981;Flay et al, 1989;Pentz et al, 1989;Schaps et al, 1986;Snow et al, 1992aSnow et al, , 1992b …”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…Drug use prevention programs are usually evaluated with longitudinal designs, which facilitate assessment of longterm program impact (Botvin et al, 1980;Evans et al, 1981;Flay et al, 1989;Pentz et al, 1989;Schaps et al, 1986;Snow et al, 1992aSnow et al, , 1992b …”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…Thus far, research has shown that educational and school-based programs for the prevention of alcohol use (Barnes, 1984) and substance abuse (Schaps, Moskowitz, Malvin, & Schaeffer, 1986), directed toward informing and educating individuals, are generally ineffective. At best, the programs may increase knowledge about alcohol and drug use, but they are much less effective in changing behavior, or even attitudes about drug use (Tobler, 1986).…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…D espite many successes in school based smoking prevention programmes, [1][2][3][4][5] several studies have suggested that such programmes are sometimes less effective than desired. Short term positive impacts tend to dissipate over time, [6][7][8][9] while several comprehensive prevention projects have failed to show positive effects.…”
mentioning
confidence: 99%